Can troponin-I be used as an independent predictor of cardiac dysfunction after supraventricular tachycardia in children with structurally normal heart? - Simovic, Aleksandra M; Tanaskovic-Nestorovic, Jelena M; Knezevic, Sanja M; Vuletic, Biljana P; Stojkovic, Andjelka K; Jeremic, Dejan M; Vulovic, Maja; Jovanović , Milan (Vojnosanitetski pregled, 2021)
Abstract Introduction. Elevated cardiac troponin gives excellent accuracy in the identification of myocardial damage in children, but it can also be elevated in a series of other diseases. Case report. We presented two children thirteen years of age with a high serum level of troponin-I after an acute episode of supraventricular tachycardia. We analyzed troponin-I levels in correlation with the maximum heart rate, duration of tachycardia and systolic left ventricular function (ejection fraction and fractional shortening). Conclusion. Abnormal troponin level can be seen in children with sustained supraventricular tachycardia and normal heart. Caution is advised in diagnosing cardiac dysfunction in children with supraventricular tachycardia and elevated troponin levels.